Phenotyping the kinematics of leaf development in flowering plants: recommendations and pitfalls. (29th May 2013) - Lièvre, Maryline; Wuyts, Nathalie; Cookson, Sarah J.; Bresson, Justine; Dapp, Mélanie; Vasseur, François; Massonnet, Catherine; Tisné, Sébastien; Bettembourg, Mathilde; Balsera, Crispulo; Bédiée, Alexis; Bouvery, Frédéric; et al.
<x xml:space="preserve">Abstract</x> Leaves of flowering plants are produced from the shoot apical meristem at regular intervals and they grow according to a developmental program that is determined by both genetic and environmental factors. Detailed frameworks for multiscale dynamic analyses of leaf growth have been developed in order to identify and interpret phenotypic differences caused by either genetic or environmental variations. They revealed that leaf growth dynamics are non‐linearly and nonhomogeneously distributed over the lamina, in the leaf tissues and cells. The analysis of the variability in leaf growth, and its underlying processes, has recently gained momentum with the development of automated phenotyping platforms that use various technologies to record growth at different scales and at high throughput. These modern tools are likely to accelerate the characterization of gene function and the processes that underlie the control of shoot development. Combined with powerful statistical analyses, trends have emerged that may have been overlooked in low throughput analyses. However, in many examples, the increase in throughput allowed by automated platforms has led to a decrease in the spatial and/or temporal resolution of growth analyses. Concrete examples presented here indicate that simplification of the dynamic leaf system, without consideration of its spatial and temporal context, can lead to important misinterpretations of the growth phenotype. WIREs Dev Biol 2013, 2:809–821. doi: 10.1002/wdev.119 Conflict of interest: The authors have declared no conflicts of interest for this article. For further resources related to this article, please visit the WIREs website.